English foreign language teachers’ awareness of childhood language impairment - Kambanaros, Maria; Giannikas, Christina N.; Theodorou, Elena (My University, 2020)
The increasing number of children with Language Impairment (LI) globally, and practitioners’ limited knowledge and specialized training can have a serious effect on foreign language learning and development. The present study proposes useful and meaningful practices in the area of raising awareness and alerting a wide range of stakeholders in the field of language education. More specifically, the study concentrates on foreign language secondary school pre-service teacher trainees and their knowledge regarding a) students’ problems in language understanding, b) why LI occurs and, c) LI intervention. This work aims to encourage collaboration among speech therapists and teachers, to foster a better understanding of each other’s expertise, and create communication-friendly classrooms that will enhance foreign language development in a supportive and inclusive learning environment.
Keywords: Intervention; Language learning; Pre-service trainees; Speech-language therapy; Teacher education